Lifestyle modification advice provided by health care professionals in the treatment and management of hypertension in Kenya - Mbogori, Teresia (International Journal Of Community Medicine And Public Health, 2020)
Background: Hypertension is one of the main modifiable risk factors for cardiovascular disease morbidity and mortality. Pharmacological and lifestyle modification approaches are used in the treatment and management of hypertension. The purpose of this study was to identify lifestyle modification advice provided to the general population and to those diagnosed with hypertension by health care providers (HCP) in Kenya. Methods: A secondary data analysis of cross-sectional data collected among 4500 Kenyans participating in the 2015 Kenya stepwise approach to surveillance study was conducted. Questions related to the consumption of salt, sugar, fat, fruits and vegetables as well as physical activity and weight management were evaluated. Results: Among all the participants, only 12.5%, 20.7%, 12.2%, 10.7%, 10.3% and 11.6% were advised to either reduce salt intake, eat 5 or more servings of fruits and vegetables, reduce fat intake, reduce intake of sugary beverages, lose or maintain weight and start or do more physical activity respectively. Of those diagnosed with HTN, 37% were advised to increase intake fruits and vegetables, 37%, 27% and 25% were advised to reduce, salt, fat and sugary beverages intake respectively, 21% and 22% were advised to start or do more physical activity and maintain a healthy body weight or lose weight respectively. Conclusions: Majority of Kenyans had not received dietary modification advice from HCP despite this being a policy recommendation in Kenya. Policy makers need to work closely with HCP to develop appropriate policy implementation strategies.